Estimativa do período reprodutivo e tamanho de primeira maturação de peixes comercialmente importantes no litoral do estado do Maranhão: uma ferramenta para a gestão pesqueira - Freitas, Jailza (2020)
The study of reproductive biology is important to determine protective measures aimed at maintaining fish stocks. Thus, the present study aims to determine and evaluate reproductive aspects of the species Nebris microps and Bagre bagre. Approximately thirty specimens of each species were collected every two months during the months from January to December 2019. The maturation stages and sex were determined through macroscopic analyzes and were confirmed with histological analysis when necessary. The analysis of maturation stages showed that for both species, there is a tendency for their reproductive period to coincide with the rainy period, confirmed by the Gonadosomatic Index (IG) and Condition Factor (K). The size of first sexual maturation for grouped sexes of the species Nebris microps was 23.3 cm and for Bagre bagre 24.1 cm. Everything indicates that the place of capture for Nebris microps is a favorable place for the species to pass through all its maturation stages of life. For Bagre bagre, capture site is a place of feeding and growth, considering that the species reproduces in the estuary. Such results can also affirm that the impact of fishing on these species, may be generating a reproduction strategy to start its first sexual maturation at younger ages